Semiotics Analysis of Balinese Culture in Wonderful Indonesia Advertisements - Noor, Habibah Aini; Erfiani, Ni Made Diana; Dewi, Ni Luh Desy Suari (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2025)
Social media, especially Instagram, plays a crucial role in digital tourism promotion by serving as a medium for cultural expression. Through visual and textual content, these platforms play a crucial role in influencing audience perceptions of cultural values, especially in tourism campaigns such as Wonderful Indonesia. This study examined the use of Charles Sanders Peirce’s semiotic theory of icon, index, and symbol in analyzing Balinese cultural representations featured in the Wonderful Indonesia Instagram advertisements. The study aims to identify sign types and the sign meaning. Using a qualitative descriptive method, five cultural themes Kuningan Day, Kecak Dance, Legong Dance, Melukat, and the Pelebon Ceremony were analyzed through textual and visual content from posts published between 2023 and 2024. The findings revealed that a total of 62 signs were identified, consisting of approximately 32 symbolic signs, 17 indexical signs, and 15 iconic signs. Symbolic signs appear consistently, reflecting their role in conveying Balinese values, rituals, and spirituality. Indexical signs refer to direct cultural elements, while iconic signs represent visual resemblance. Then focused on the sign meanings in each cultural element to gain a deeper understanding of the values, rituals, and spiritual significance conveyed through the advertisements.